Nilai-Nilai Pendidikan dari Q.S Al-Anfal Ayat 27-28 tentang Dasar – Dasar Pendidikan Akhlak Mulia dalam Membentuk Sikap Amanah - Muna Nabila; Fitroh Hayati (Bandung Conference Series: Islamic Education, 2024)
Abstract. Amanah is one of the commendable qualities that must be possessed by a Muslim, where the nature of trust is the nature of carrying out all the responsibilities entrusted to someone in accordance with what is mandated without deviating in the slightest. The implementation of the mandate can provide welfare and justice to others. The purpose of this study is to compare to find the similarities of the two concepts of trust in the Koran an-Nisa verse 58 between the interpretations of alMisbah and al-Azhar. This research method uses library research method. The primary data source in this study is the book of interpretations of al-Misbah and alAzhar, secondary data sources are books or reading materials related to the interpretation of al-Misbah and al-Azhar in Surah an- Nisa verse 58. The results of the study formulate the conclusion that in the interpretation of al-Misbah amanah is that which has been handed over to those who are entitled to receive it, it should be carried out perfectly and on time, the same thing according to the interpretation of alAzhar, the mandate should be handed over to experts according to their abilities and talents, the latter is more directed in terms of leadership. However, there are different interpretations of trust, according to al-Misbah's interpretation something that is handed over or entrusted to another party to be maintained and returned when the time comes to its owner, while trust according to al-Azhar's interpretation is something that is guarded to be conveyed to its owner. Abstrak. Amanah merupakan salah satu sifat terpuji yang harus dimiliki oleh seorang muslim, dimana sifat amanah adalah sifat melaksanankan segala tanggungjawab yang dipercayakan kepada seseorang sesuai dengan yang diamanahkan tanpa menyimpang sedikitpun. Pelaksanaan amanah dapat memberi kesejahteraan dan keadilan kepada orang lain. Tujuan penelitian ini adalah membandingkan untuk menemukan persamaan dari dua konsep amanah dalam al-Quran surat an-Nisa ayat 58 antara tafsir al-Misbah dan al- Azhar. Metode penelitian ini menggunakan metode library research. Sumber data primer dalam penelitian ini adalah kitab tafsir al-Misbah dan al-Azhar, sumber data skunder adalah buku atau bahan bacaan yang terkait dengan tafsir al-Misbah dan al-Azhar surat an-Nisa ayat 58. Hasil penelitian merumuskan kesimpulan bahwa dalam tafsir al-Misbah amanah adalah yang telah diserahkan kepada yang berhak menerimanya hendaklah ditunaikan secara sempurna dan tepat pada waktunya, hal yang sama menurut tafsir alAzhar amanah hendaklah diserahkan kepada ahlinya yang sesuai dengan kesanggupan dan bakatnya, yang terakhir ini lebih mengarah dalam perkara kepemimpinan. Namun terdapat perbedaan penafsiran tentang amanah, menurut tafsir al-Misbah sesuatu yang diserahkan atau dititipkan kepada pihak lain untuk dipelihara dan di kembalikan bila tiba saatnya kepada pemiliknya, sedangkan amanah menurut tafsir al-Azhar yaitu sesuatu yang di jaga untuk disampaikan kepada pemiliknya.